PENERAPAN SISTEM ANTRIAN PELAYANAN (SIAP) - Gusty Setyono (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2020)
SIAP (Service Queuing System) application is an innovation in terms of service queues. SIAP is an android based application developed as a form of innovation for better service by considering technological developments to the public. This application provides a registration menu to people who want to do service. By entering the ID number, name and type of service, the registrant (community) can get a queue number. After the community registers, the registrants will be verified by the administrator. After being verified, the registrant gets a queue number. After the registrant gets a queue number then he can immediately come to the Administrative Services and Civil Registration Service to receive services in accordance with the order of the queue number in the SIAP Application. After carrying out the service, the community can see the service status. In addition, there is also a feature of complaints from the public if there are irregularities in the service that are directly conveyed to the leadership without going through the administrator or staff. Keyword : SIAP (Service Queuing System), service, application, administrator.